Manejo integrado de mosca de la fruta Anhastrepha fraterculus (Wiedemann 1830) en el cultivo de naranja Citrus sinensis (Osbeck 1765). - Ayala Guerrero, Roger Damián (2023)
The present investigation was based on collecting information on the Integrated Management of the fruit fly Anhastrepha fraterculus (Wiedemann 1830) in the cultivation of orange Citrus sinensis (Osbeck 1765), different sources of information tell us that this crop is of economic importance, due to contribute to the feeding of the world population and why not say it at the national level. This crop is characterized by having a yellow fruit in different shades with a globose or oblong shape. It is used for fresh consumption as seasonal fruit or for juice extraction. It is also used in the food industry for the production of juices, liqueurs, jams, pectins, jellies and confectionery products. It is a highly prized crop for its vitamin C content. The yield of the orange crop is constantly threatened by phytosanitary problems, including pest insects, according to the sources consulted inform us that A. fraterculus develops quickly and its highest incidence in its larval stage causes considerable losses for the small and medium farmers. There are different control methods that can help reduce the incidence of the pest and therefore a C. sinensis orange crop free or in a controlled way from the fruit fly. In this investigation we deal with the different methods or types of control of the fruit fly, different types of trapping can also be used.